Cartera vencida en el Gobierno Autónomo Descentralizado Parroquial de Febres Cordero en el periodo 2022. - Herrera Meza, Edwin Oswaldo (2023)
The collection of taxes paid by the citizens of the Parroquial Decentralized Autonomous Government of De Febres Cordero is a very important item for this entity since it is a great source of income. The Parochial Decentralized Autonomous Government of Febres Cordero has different types of income and is made up of: the transfer from the central government, financial loans and the own income that it may generate. Overdue portfolios are obligations of a taxpayer when the outstanding debt has not been paid, which is why they are considered overdue, and represent a problem for companies because they create value that has not yet been recovered and affect their liquidity. Portfolio management is the organization of the financial assets we own with the aim of reducing risk and increasing profitability. This includes making informed investment decisions and using commercial strategies, which is why it is essential to generate an analysis of the overdue portfolio in the Parochial Decentralized Autonomous Government of Febres Cordero in the period 2022. the main objective of the investigation, which is to determine whether The expired portfolio of the Parochial Decentralized Autonomous Government of Febres Cordero, in the period 2022, affects the quality of the services offered to the citizens of the Febres Cordero parish. The type of research was non-experimental with a cross-sectional design with the purpose of collecting data and information on the proposed topic in order to conclude with the specific problem and the solution to it.